2018
DOI: 10.1186/s12977-018-0415-4
|View full text |Cite
|
Sign up to set email alerts
|

The HTLV-1 oncoprotein Tax is modified by the ubiquitin related modifier 1 (Urm1)

Abstract: BackgroundAdult T-cell leukemia/lymphoma (ATL) is an aggressive malignancy secondary to chronic human T-cell lymphotropic virus 1 infection, triggered by the virally encoded oncoprotein Tax. The transforming activity and subcellular localization of Tax is strongly influenced by posttranslational modifications, among which ubiquitylation and SUMOylation have been identified as key regulators of the nuclear/cytoplasmic shuttling of Tax, as well as its ability to activate NF-κB signaling.ResultsAdding to the comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
(38 reference statements)
0
7
0
1
Order By: Relevance
“…Further work in cultured human T cells also demonstrated that Tax1, but not Tax2, induces expression of OX40L, a tumor necrosis factor ligand, by binding to an IKK [ 63 ]. This and additional studies corroborate to show NF-κB signaling becomes misregulated when Tax1 is over-expressed [ 58 ], demonstrating how data from Drosophila can facilitate the understanding of why related viruses can cause different diseases in humans.…”
Section: Innate Immune Signaling Pathways and Pathogenic Proteins mentioning
confidence: 53%
See 1 more Smart Citation
“…Further work in cultured human T cells also demonstrated that Tax1, but not Tax2, induces expression of OX40L, a tumor necrosis factor ligand, by binding to an IKK [ 63 ]. This and additional studies corroborate to show NF-κB signaling becomes misregulated when Tax1 is over-expressed [ 58 ], demonstrating how data from Drosophila can facilitate the understanding of why related viruses can cause different diseases in humans.…”
Section: Innate Immune Signaling Pathways and Pathogenic Proteins mentioning
confidence: 53%
“…These modifications are considered to alter the activity, turnover, and subcellular localization of Tax1 [ 57 ]. Work in Drosophila combined with human cell-based assays identified a novel posttranslational modification on Tax1 and demonstrated the in vivo significance of this alteration [ 58 ]. In this study, Hleihel et al first showed that Tax1 could undergo Urmylation, a process in which Urm1 (Ubiquitin-related modifier 1), a ubiquitin-like protein, is covalently conjugated to the target protein [ 59 ] ( Figure 1 ).…”
Section: Innate Immune Signaling Pathways and Pathogenic Proteins mentioning
confidence: 99%
“…RNA was extracted [ 23 , 24 , 25 , 26 ] from colon tissues using Qiazol (Qiagen, Hilden, Germany) as per manufacturer recommendations. For this purpose, 1 mL of the Qiazol reagent was added to 100 mg of mouse colon tissue and the sample was then homogenized using a Biospec Tissue Tearor (Bartlesville, OK).…”
Section: Methodsmentioning
confidence: 99%
“…According to this report, Urm1 is conjugated to the viral oncoprotein Tax in human and fly models, leading to Tax redistribution to the cytosol thereby promoting adult T-cell leukemia (ATL). Interestingly, the localization of Tax is also controlled by ubiquitin and SUMO [ 106 ].…”
Section: Molecular Phenotypes and Implications For Higher Organismmentioning
confidence: 99%